Macro-brothels as crime attractors: impact of closure, displacement, and diffusion of benefits - Soto, Carles (European journal of criminology, 2020)
Efforts made at preventing prostitution - and any associated crime and disorder - are sometimes undermined by assumptions the problem will likely displace elsewhere. This study measures changes in local crime rates following the closure of two macro-brothels in Castelldefels, a town in the greater metropolitan area of Barcelona, Spain. The closures were complemented by a local ordinance aimed at preventing spatial displacement. Weighted displacement quotients indicated that the modest crime reductions observed in the treatment area (immediately around the macro-brothels) did not displace to the buffer area (the rest of the town); instead, a diffusion of benefits was observed, whereby crime reductions were also observed in the buffer area. The implications of the findings for criminological theory, policy and practice are discussed.